PART X – October 1967 – Communications - On the Relation of the Terminal Solubility of Hydrogen to the Ductility Drop in Vanadium - C. V. Owen; D. H. Sherman; T. E. Scott (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
It has been established' that vanadium exhibits a ductile to brittle transition temperature which increases with increasing hydrogen content. Optical microscopic examination at room temperature revealed no evidence of hydride precipitate in fractured specimens containing 100 ppm H, but hydrides were present in samples with 800 ppm H. More recently2 the strain rate and temperature dependences of the ductility drop in vanadium containing 6 ppm H were reported. It was argued that the ductile-brittle transition, while dependent on the presence of hydrogen, probably could not be explained by the precipitation of hydride. The bases of the argument were that 6 ppm H would not produce sufficient hydride to alter the ductility to the extent observed and no visual evidence of hydride was obtained. However, the data were not sufficient in these investigations 1,2 to define accurately the ductile-brittle transition temperature. Also, no information was available concerning the terminal solubility of hydrogen in vanadium at the low concentrations employed. westlake 3 has studied the electrical resistivity of vanadium at several hydrogen concentrations. He was able to detect the precipitation of hydride and to extend the hydrogen solvus to the composition and temperature range pertinent to the observed ductile-brittle transition behavior, Westlake compared his